Bioethanol and biogas production: an alternative valorisation pathway for green waste. (June 2022) - Sofokleous, M.; Christofi, A.; Malamis, D.; Mai, S.; Barampouti, E.M.
Abstract: Biofuels are a research field of great interest given the environmental benefits they offer over conventional fossil fuels. Nowadays, it is urgent to find ways of utilizing waste in the direction of biofuels production. The aim of this paper was the utilization of green waste (branches, leaves and ligno-cellulosic residues from tree prunings, hedge cuttings and grass clippings) towards biofuels production and specifically towards bioethanol and biogas. The experimental plan that was followed included biogas production through anaerobic digestion and bioethanol production through alcoholic fermentation after the necessary chemical pretreatment (acid or alkaline hydrolysis) prior to enzymatic hydrolysis and fermentation. Based on the results obtained, three valorisation scenarios of green waste were designed and compared in terms of product mass intensity, product yield and energy content of biofuels produced. The optimal results for bioethanol production were 5.22 g/L ethanol, 70.61% saccharification yield and 33.67% ethanol yield with acid pretreatment using H2 SO4 3% w/v, 475 μL/g cellulose CellicCtec2 and 10% solids loading. Regarding biogas, the highest biogas production observed was 267.1 mL biogas/g dry substrate resulting from anaerobic digestion of the alkaline stillage. Thus, the production of biofuels from green waste is technically feasible, although it provides moderate efficiencies. However, for a sustainable valorisation of green waste, other techno-economic factors such as the cost of enzymes, chemicals, energy, etc. must be taken into account. Graphical abstract: Image 1 Highlights: Bioethanol and biogas production from green waste is technically feasible. Alternative valorisation scenarios were proposed. The process mass intensity index for all scenarios is close to 1, indicating sustainable solutions. The higher product yield was achieved by applying just anaerobic digestion (AD). Τhe highest energy content of the biofuels included alkaline pretreatment, enzymatic hydrolysis and fermentation and AD.